Evaluasi Website Kuliah Online STMIK Amikom Purwokerto Menggunakan Metode Heuristik (Studi Kasus Mata Kuliah Enterprise Resource Management) - Debby Ummul Hidayah; Ika Romadoni Yunita; Gustin Setyaningsih (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
Online lecture is one alternative to support distance learning. STMIK Amikom Purwokerto has implemented the online lecture system. In order to support effective learning while studying online using website media, an effective web interface is needed. However, there were complaints from users when accessing web lectures online. One of them is the user does not understand the overall use of functions on the existing system. Therefore heuristic evaluation is needed to find out how useful the system is in supporting online lectures. The results show that based on the calculation results using heuristic evaluation, the severety rating with a scale of 3 means that the online learning website at STMIK Amikom Purwokerto needs to be throughly improved from both system functionality and interface design.